2009
DOI: 10.1007/s00406-009-0024-2
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis and psychosis/schizophrenia: human studies

Abstract: The association between cannabis use and psychosis has long been recognized. Recent advances in knowledge about cannabinoid receptor function have renewed interest in this association. Converging lines of evidence suggest that cannabinoids can produce a full range of transient schizophrenia-like positive, negative, and cognitive symptoms in some healthy individuals. Also clear is that in individuals with an established psychotic disorder, cannabinoids can exacerbate symptoms, trigger relapse, and have negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
158
0
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(176 citation statements)
references
References 237 publications
(268 reference statements)
5
158
0
13
Order By: Relevance
“…Its use in youth increases the risk of developing psychosis, with an estimated odds ratio of 2.10-2.93 (Henquet et al, 2005;Moore et al, 2007), decreasing the age of schizophrenia onset (Sugranyes et al, 2009). The neurobiological mechanisms underlying this increased psychosis susceptibility are poorly understood (D'Souza et al, 2009;Gage et al, 2013). However, some studies have found that frequent cannabis exposure may downregulate AEA signalling in patients with schizophrenia, but not in healthy individuals (Leweke et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Its use in youth increases the risk of developing psychosis, with an estimated odds ratio of 2.10-2.93 (Henquet et al, 2005;Moore et al, 2007), decreasing the age of schizophrenia onset (Sugranyes et al, 2009). The neurobiological mechanisms underlying this increased psychosis susceptibility are poorly understood (D'Souza et al, 2009;Gage et al, 2013). However, some studies have found that frequent cannabis exposure may downregulate AEA signalling in patients with schizophrenia, but not in healthy individuals (Leweke et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis use is highly comorbid with schizophrenia (Koskinen et al, 2010) and considered a component cause of the disorder (D'Souza et al, 2009;Murray et al, 2007). There is growing evidence that long-term or heavy cannabis use impacts upon brain structure and function, particularly in regions known to be affected in schizophrenia, such as the hippocampus (Ashtari et al, 2011;Lorenzetti et al, 2010;Solowij and Michie, 2007;Solowij et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…16,24,25 In addition to the above immediate toxicities, there is concern over long-term SC use, as chronic use of marijuana has been associated with increased rates of schizophrenia and possible memory loss. 38,39 …”
Section: Synthetic Cannabinoidsmentioning
confidence: 99%